1995
DOI: 10.1104/pp.108.2.721
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Sustained Component of Nonphotochemical Quenching of Chlorophyll Fluorescence in Isolated Chloroplasts and Leaves of Spinach

Abstract: When leaves are exposed to intensities of light in excess of those that can be used with maximum quantum efficiency, the excess energy is dissipated nonphotochemically; this is detected as the quenching of Chl fluorescence and the process is therefore referred to as nonphotochemical quenching, qN (for reviews, see Demmig-Adams and Adams, 1992;Horton and Ruban, 1992;. The heterogeneous nature of qN has been revealed by the study of its relaxation in darkness or after application of inhibitors (Horton and Hague,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 17 publications
3
54
0
1
Order By: Relevance
“…There is additional complexity because the activity of the violaxanthin deepoxidase, which determined the DEPS, was dependent on the lumen pH (Pfü ndel and Bilger, 1994;Eskling et al, 1997), and this dependency was also subject to light activation (Delrieu, 1998). It is also important to point out that the development of the light-activated state, for both chloroplasts and leaves, was associated with a sustained qN and an associated decrease in F v /F m , which is in agreement with previous work (Ruban and Horton, 1995a).…”
Section: Discussionsupporting
confidence: 78%
“…There is additional complexity because the activity of the violaxanthin deepoxidase, which determined the DEPS, was dependent on the lumen pH (Pfü ndel and Bilger, 1994;Eskling et al, 1997), and this dependency was also subject to light activation (Delrieu, 1998). It is also important to point out that the development of the light-activated state, for both chloroplasts and leaves, was associated with a sustained qN and an associated decrease in F v /F m , which is in agreement with previous work (Ruban and Horton, 1995a).…”
Section: Discussionsupporting
confidence: 78%
“…The data showing that preceding sowing incubation of seeds in ZEN solutions resulted in an increase in the nonphotochemical quenching (qE, qT) during strong illumination for both species (Table 4) are consistent with the opinions of other authors (Fork and Satoh 1986;Horton and Hauge 1988;van Wijk and van Hasselt 1993;Ting and Owens 1994;Ruban and Horton 1995;Owens 1996;Haldrup et al 2001) that such response may be recognized as the action of the first defense line for the photosynthetic apparatus against photoinhibitory injuries and other photooxidative ones. In our experiment it was observed that ZEN prevented photoinhibitory injuries during strong illumination due to the safe dissipation of the excess of absorbed light energy through mechanisms related to the development of pH gradient (qE) in thylakoids and phosphorylation of LHC2 (qT).…”
Section: Photoinhibitory Reactions Of Psiisupporting
confidence: 77%
“…The non-photochemical quench qN is based on three major constituents: the energy quenching qE, qT and qI caused by a photoinhibition of PSII units (Fork and Satoh 1986;Horton and Hauge 1988;van Wijk and van Hasselt 1993;Ting and Owens 1994;Ruban and Horton 1995;Owens 1996;Haldrup et al 2001). qE is thought to occur in PSII antennae and there is evidence that it is regulated by the pH gradient across the thylakoid membrane and by the interconversion of pigments in the xanthophylls cycle (Owens 1996;Ting and Owens 1994;Ruban and Horton 1995). The photoinhibitory quenching qI is caused by the photoinhibition of PSII units (Greer et al 1986;Baker 1994;Owens 1996).…”
Section: Measurements Of Psii Photoinhibitionmentioning
confidence: 99%
“…Previous work led to different proposals for mechanisms leading to fluorescence recovery components with intermediate half-life between qE and qI. First, it was attributed to state 1-state 2 transitions [43]; second to PSII photoinhibition [51]; third to a slowly developing component of qE dependent on Zea [52]; fourth to light-induced dissociation of the complex Lhcb4-Lhcb6-LHCII-M [19]. Here, we show that qM did not correlate with Zea accumulation nor was it related to qI.…”
Section: (C) Chloroplast Avoidance Response and Qmmentioning
confidence: 99%